The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/acer.13436
|View full text |Cite
|
Sign up to set email alerts
|

Acute Alcohol Exposure and Risk of Mortality of Patients with Traumatic Brain Injury: A Systematic Review and Meta-Analysis

Abstract: After traumatic brain injury (TBI), patients usually live with significant disability and socioeconomic burdens. Acute exposure to alcohol is considered a major risk factor for TBI. Numerous studies have examined whether alcohol exposure is related to the risk of mortality in patients with TBI, yet the results remain inconsistent. We performed a meta-analysis to assess whether acute alcohol exposure affects the mortality rate of TBI patients. We searched PubMed, EMBASE, and the Cochrane Library up to November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…1 Other studies found positivity in 22.8% and 37% respectively. 9 10 Our values are similar to those found in these same bibliographic citations. 9 10 When comparing our data with those found by Faria (2008) 11 who observed a positive blood alcohol level of 39.3%, it can be inferred that under the conditions of the dry law, there is no significant difference.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1 Other studies found positivity in 22.8% and 37% respectively. 9 10 Our values are similar to those found in these same bibliographic citations. 9 10 When comparing our data with those found by Faria (2008) 11 who observed a positive blood alcohol level of 39.3%, it can be inferred that under the conditions of the dry law, there is no significant difference.…”
Section: Discussionsupporting
confidence: 90%
“…9 10 Our values are similar to those found in these same bibliographic citations. 9 10 When comparing our data with those found by Faria (2008) 11 who observed a positive blood alcohol level of 39.3%, it can be inferred that under the conditions of the dry law, there is no significant difference. Our study was performed under Decree 6,489 of 19/06/2008, which in turn became Law 11,705, popularly known as the Dry Law, and other laws that prohibited the sale of alcohol due to the Covid-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…[ 29 ] Among TBI patients with positive blood alcohol concentration, the moderate to high concentration group showed lower in-hospital mortality than the lower concentration of alcohol group. [ 7 ] Animal studies have postulated a neuroprotective effect of alcohol, including less reduction of cerebral blood flow, more normal glucose metabolism, higher corticosterone values, and less impairment of motor and cognitive functions, which can be neuroprotective. [ 15 , 30 ] However, in experimental study of TBI and hemorrhagic shock porcine model, ethanol administration decreased survival time, impaired the hemodynamic response, and worsened measures of cerebral tissue perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…[19] In addition, we categorized GCS (alert [15]. verbal [13][14], pain [9][10][11][12], and unresponsive [3][4][5][6][7][8]), [23] AIS (mild [1][2] and severe [3][4][5][6]), [24] and NISS (mild [1][2][3][4][5][6][7][8], moderate [9][10][11][12][13][14][15], severe [16][17][18][19][20][21][22][23][24], and very severe ). [25] In our analysis, we dealt with missing data using a multiple imputation approach for reducing the potential bias that might arise from listwise deletion of cases with missing values.…”
Section: Study Outcomes and Variablesmentioning
confidence: 99%
See 1 more Smart Citation